Bringing Online Learning to Campus: The Hybridization of Teaching and Learning at Brigham Young University - Waddoups, Gregory L.; Howell, Scott L. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2002)
The primary purpose of Brigham Young University (BYU) is to provide students with a combination of sacred and secular education often described as the “BYU experience.” Achieving this purpose is challenged by the rapid growth in Church membership and an enrollment cap of 30,000 students. To address these challenges, BYU sponsors the use of technology to bridge the gap between the increased Church membership and the number of students allowed under the enrollment caps. This institutional case study shows how these challenges have influenced the hybridization of teaching and learning for on campus (resident) and off campus (distance) students. It also describes how BYU has brought distance education to campus, and is beginning to bring campus-based educational practices to distance education.